An outbreak of SARS-CoV-2 omicron variant and deaths of three lions in a zoo - Kuroda, Yudai; Ozaki, Miki; Sakai, Yusuke; Uchida-Fujii, Eri; Hanada, Ikumi; Yamamoto, Tsukasa; Tatemoto, Kango; Hirata, Yuichiro; Sato, Yuko; Katano, Harutaka; Nagata, Noriyo; Kato, Hirofumi; et al. (One health, 2024)
There have been reports of the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from humans to various mammalian species. Some infected animals show clinical signs and may even die in rare cases. Outbreaks of SARS-CoV-2 have been reported in zoos where susceptible animals are bred in high population densities. However, there have been few reports of omicron variant outbreaks in zoo animals. From late 2022 to 2023, an outbreak of the SARS-CoV-2 omicron variant occurred in one Japanese zoo. A total of 24 lions were housed in the zoo; 13 of them showed respiratory symptoms, and the three oldest lions died. Molecular and histopathological analyses revealed that the deceased lions were infected with SARS-CoV-2 omicron BF.7.15. Virus-neutralization tests showed that all 21 lions were positive for antibodies against the omicron variant, but not against the delta variant. In addition, three tigers and one bear in the same or neighboring building as the lions possessed antibodies against the omicron variant. This is a very rare report on the outbreak of a SARS-CoV-2 omicron variant infection that resulted in the death of animals. This finding demonstrates the importance of continuous countermeasures to protect non-vaccinated animals from SARS-CoV-2 infection.